A prospective study of specimen eversion to lateral rectum and valgus resection for low rectal cancer - Qian, Long; Huang, Xiaoxu; Xu, Li; Chen, Hao; Cao, Tingting; Wang, Song; Luo, Can; Xia, Yabin (Frontiers in Surgery, 2022)
Purpose: To investigate the safety and efficacy of a reverse puncture device and specimen eversion of the rectum for resection in total laparoscopic proctectomy. Methods: In a prospective study from August 2019 to March 2021, 40 patients underwent a procedure with a reverse puncture device and specimen eversion of the rectum for resection in total laparoscopic low rectal cancer resection, that is, natural orifice specimen extraction surgery (the NOSES group). Forty patients in the control group were treated with conventional laparoscopic radical resection of low rectal cancer (the LAP group).Intraoperative- and postoperative-related indicators, recovery, inflammatory factors, quality of life and mental health were compared. Results: All operations were successfully completed . Compared with the LAP group, the NOSES group had better short-term outcomes, such as eating time, postoperative pain, and especially postoperative incision-related complications. At the same time, postoperative inflammatory factor levels, psychological trauma, life-related anxiety and depression scores, and patient’s quality of life were better than those of the LAP group. Conclusions: The application of a reverse puncture device and specimen eversion of the rectum for resection in total laparoscopic low rectal cancer resection is a technically feasible and safe approach that has a short-term curative effect.